Diagnóstico del comportamiento de arcillas en el distrito de Chiclayo, departamento de Lambayeque - Medrano Lizarzaburu, Eithel Yván (2022)
Conferencia de la 2nd LACCEI International Multiconference on Entrepreneurship, Innovation and Regional Development - LEIRD 2022: “Exponential Technologies and Global Challenges: Moving toward a new culture of entrepreneurship and innovation for sustainable”, Virtual Edition, December 5 – 7.